The positive impact of robotic‐assisted BCR TKA on post‐operative joint line restoration, lateral posterior condylar offset and standard and advanced activity in the 2011 Knee Society Score than the conventional jig‐based technique - Takao Kaneko; Kosuke Shiga; Ayakane Yamamoto; Kazuki Amemiya; Masaru Omata; Shu Yoshizawa (Journal of Experimental Orthopaedics, 2025)
Abstract Purpose The aim of this study was to compare post‐operative short‐term patient‐reported outcome measurements (PROMs) between robotic‐assisted (RA) and the conventional jig‐based technique using bi‐cruciate retaining total knee arthroplasty (BCR TKA). Methods This retrospective single‐surgeon consecutive cohort analysis compares 33 RA‐BCR TKA patients (Robot group) to 32 conventional TKA patients (Conventional group). Lateral distal femoral angle (LDFA), medial proximal tibial angle (MPTA), femoral and tibial component rotational alignment, distal and posterior femoral osteotomy (mm) were compared between the two groups using three‐dimensional computed tomography (3DCT) measurements. 2011 Knee Society Score (KSS), Western Ontario and McMaster Universities Arthritis Index (WOMAC), Forgotten Joint Score and Patella score were collected more than 1 year after surgery. Results Pre‐operative knee scores were significantly higher in the Robot group (mean: 20.5) than in the Conventional group (mean: 16.8), while functional scores were significantly lower in the Robot group (mean: 57.7) than in the Conventional group (mean: 69.6). The Robot group showed significantly greater improvements in post‐operative extension angle (p < 0.01), and standard and advanced activity in the 2011 KSS (p < 0.01). LDFA, MPTA and rotational alignment of the femoral and tibial components showed no significant difference between the two groups. Medial distal femoral osteotomy (mm) was significantly greater in the Conventional group (p < 0.01). Lateral posterior femoral osteotomy (mm) was significantly greater in the Robot group (p < 0.01). The robotic group had significantly more cases of joint line restoration and reduced lateral posterior condylar offset than the Conventional group. Conclusions RA‐BCR TKA improved post‐operative extension angle and standard and advanced activity in the 2011 KSS more than the Conventional TKA. Level of Evidence Level III.